2020
DOI: 10.2147/jmdh.s237101
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive Factors Associated to Pediculosis Preventive Behaviors Among Mothers of School-Age Children in Chaldoran County, Iran</p>

Abstract: Background: Despite the improvement of living standards and public health as well as conducting the specific programs based on pediculosis control guidelines, Head Lice Infestation (HLI) is still a worldwide health concern. The purpose of this study was to investigate the cognitive factors associated to school-age children's HLI among mothers in an urban community. Subjects and Methods: In this cross-sectional study, a multi-stage cluster random sample of 619 mothers of students in elementary schools of Chaldo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…While after the intervention, the ratio has changed significantly. Our findings are in line with studies of [ 29 ] and [ 33 ] that previously measured the level of parental learning in health education programs for pediculosis. Despite this significant decrease in the prevalence rate, the eradication was not achieved, which seems to be due to the short duration of intervention and control.…”
Section: Discussionsupporting
confidence: 92%
“…While after the intervention, the ratio has changed significantly. Our findings are in line with studies of [ 29 ] and [ 33 ] that previously measured the level of parental learning in health education programs for pediculosis. Despite this significant decrease in the prevalence rate, the eradication was not achieved, which seems to be due to the short duration of intervention and control.…”
Section: Discussionsupporting
confidence: 92%
“…While, after the intervention, the ratio has changed signi cantly. Our ndings are in line with studies of [28] and [35] that previously measured the level of parental learning in health education programs for pediculosis. Despite this signi cant decrease in the prevalence rate, the eradication was not achieved, which seems to be due to the short duration of intervention and control.…”
Section: Discussionsupporting
confidence: 92%
“…The high occurrence of unhealthy behaviors (e.g., not bathing, not combing) among head lice infested people was alarming, which had also been reported by Nejati et al [27] and Nezhadali et al [28] among female students. One study in Indonesia on pediculosis preventive behaviors among female students demonstrated many respondents with mild actions had practiced moderate prevention, whereas a small proportion of respondents with bad behavior groups these avoidance had been poorly done [29].…”
Section: Discussionmentioning
confidence: 55%